Design and Management of Web-Based Innovation Communities: A Lifecycle Approach - Hallerstede, Stefan; Bullinger-Hoffmann, Angelika; Möslein, Kathrin (Eighteenth Americas Conference on Information Systems, 2012)
Nowadays, web-based communities are a popular means to integrate external innovators into the innovation process of organizations. Combining extant research in innovation management and IS management, we integrate open innovation and application lifecycle management (ALM) to present an integrated understanding of the design and management of innovation communities. Therefore, the paper draws on an in-depth explorative case study. We describe the process of community design and management along the phases of ALM. From a socio-technical systems perspective, the manager of an innovation community has to specialize in designing and managing the social subsystem rather than the technical subsystem of an innovation community. Accordingly, we reveal that the community manager’s core asset is a specialized backend that supports these management tasks.
WiSo-Import:2015-04-17:4277
Keywords: Socio-Technical Systems; Open innovation; innovation community; Case study; Application Lifecycle Management